Transdermal delivery of tolterodine tartrate for overactive bladder treatment: In vitro and in vivo evaluation - Rajabalaya Rajan; Mun Chung Yee; Chellian Jestin; Chakravarthi Srikumar; David Sheba R. (Acta Pharmaceutica)
The purpose of the study was to develop a transdermal tolterodine tartrate (TT) patch and to analyse its efficacy for overactive bladder (OAB) treatment. Patches were prepared using various polymers and plasticizers via the solvent casting method. The patches were characterized for tensile strength, thickness, moisture content, modulus of elasticity and water absorption capacity. Differential scanning calorimetry and Fourier transform infrared analyses were also performed. To determine patch effectiveness, in vitro release, permeation and animal studies were performed. The patches showed satisfactory percentage of release, up to 89.9 %, and their mechanical properties included thickness (0.10–0.15 mm), tensile strength (4.62–9.98 MPa) and modulus of elasticity (20–29 MPa). There were no significant interactions between TT and other excipients. Animal studies indicated that the TT patch reduced the incidence of side effects; however, studies of longer duration are required to determine the effectiveness in treating OAB.